Development of Electropneumatic Simulation Learning Media based on Virtual Reality for Increasing Students' Competence Skills in Industrial Automation Engineering of Vocational School - Sugiarto, Hariyadi; Hatmojo, Yuwono Indro (Elinvo (Electronics, Informatics, and Vocational Education), 2024)
This research and development aim to (1) know the development step of Electropneumatic simulation learning media based on Virtual Reality for increasing students' competence skills in Industrial Automation Engineering; (2) create a proper Electropneumatic simulation learning media based on Virtual Reality for increasing students' competence skill in Industrial Automation Engineering; (3) analyze the effectiveness level of Electropneumatic simulation learning media based on Virtual Reality for increasing students' competence skill and response in Industrial Automation Engineering. This research and development used the ADDIE model (Analyze, Design, Develop, Implement, Evaluate). The effectiveness level of virtual reality media was analyzed using n-gain data from the pre-test and post-test enhancement score results. The results of this research and development are as follows: (1) the developed virtual reality media worked well after passing the functional test by using the Black Box testing method; (2) the development of the Virtual Reality learning media received an average score of 87.77% from three media experts and an average score of 88.75% from two subject matter experts. Based on these average scores, virtual reality learning media is categorized as "VERY PROPER" and can be used as a learning medium for practicum; (3) the use of Virtual Reality was effective in increasing students' competence skills and response, based on the hypothesis testing results using a Paired Sample T-test, a Sig. (2-tailed) value of 0.129 > 0.05.The development research encountered several limitations, such as the high cost of Virtual Reality devices, students' unfamiliarity with Virtual Reality technology causing discomfort, and the extended time required for students to become proficient in operating Virtual Reality devices.